Rhizomes of Eremostachys laciniata: Isolation and Structure Elucidation of Chemical Constituents and a Clinical Trial on Inflammatory Diseases - Abbas Delazar; Satyajit D. Sarker; Lutfun Nahar; Shahriar Barzegar Jalali; Masoud Modaresi; Sanaz Hamedeyazdan; Hossein Babaei; Yousef Javadzadeh; Solmaz Asnaashari; Sadeighe Bamdad Moghadam (Tabriz University of Medical Sciences, 2013)
Purpose: The purpose of this study was the isolation and structure elucidation of chemical compounds from the rhizomes of Eremostachys laciniata (L) Bunge (EL), an Iranian traditional medicinal herb with a thick root and pale purple or white flowers as well as the clinical studies on the therapeutic efficacy and safety of topical application of the EL extract in the management of some inflammatory conditions, e.g., arthritis, rheumatoid arthritis and septic arthritis (Riter's syndrome). Methods: The structures of the isolated compounds were elucidated unequivocally on the basis of one and two dimensional NMR, UV and HR-FABMS spectroscopic data analyses. A single-blinded randomized clinical trial was carried out with the extract of the rhizomes of E. laciniata (EL) to determine the efficacy and safety of the traditional uses of EL compared to that of piroxicam in treatment of inflammatory diseases, e.g., osteoarthritis, rheumatoid arthritis and Reiter's syndrome. Results: Eleven iridoid glycosides, two phenylethanoids and two phytosterols were isolated and identified for the first time from the rhizomes of EL. After 14 days of treatment with the EL and piroxicam ointments, all groups showed significant improvements compared to the control groups. EL (5%) ointment induced better initial therapeutic response than piroxicam (5%) onitment. Conclusion: This clinical trial established that EL was suitable for topical applications as a safe and effective complementary therapy for inflammatory diseases.